An Analysis Students’ Problems in Writing Recount Text at The Eighth Grade Students of SMPN 1 Pangkalan Koto Baru - Fakhruzi Fakhruzi; Friska Ratna Sari Purba; Aryuadi Aryuadi (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by the low ability of students in writing recount texts at SMAN 2 Kuok. This study aims to determine students' problems in writing recount text in class XI students at SMAN 2 Kuok. This study uses a qualitative research design. Class X SMPN 1 Pangkalan Koto Baru consists of 21 students. The sampling technique used was purposive sampling. The instrument used in this research is a questionnaire. Data were analyzed by describing students' problems in writing recount text based on the results of the questionnaire. the researcher found that students had 4 problems in writing recount text, namely vocabulary, organization, mechanics and grammar. Based on the results of the analysis of the questionnaire, 81% of students had difficulty using grammar while 56.2% of students had difficulty understanding concept of vocabulary. Keywords: Writing Problem, Recount Text, Junior High School